Whole-Body Regeneration Methods and Protocols - Blanchoud, Simon; Galliot, Brigitte (Methods in Molecular Biology, 2022)
This Open Access volume provides a comprehensive overview of the latest tools available to scientists to study the many facets of whole-body regeneration (WBR). The chapters in this book are organized into six parts. Part One provides a historical overview on the study of the WBR phenomena focusing on the primary challenges of this research. Parts Two and Three explore a series of non-vertebrate zoological contexts that provide experimental models for WBR, showing how they can be approached with cellular tools. Parts Four, Five, and Six discuss the future advancements of WBR, reporting about the cutting-edge techniques in genetics and omics used to dissect the underlying mechanisms of WBR, and systems biology approaches to reach a synthetic view of WBR. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratoryprotocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and thorough, Whole-Body Regeneration: Methods and Protocols is a valuable resource for scientists and researchers who want to learn more about this important and developing field.